2017
DOI: 10.1016/j.ccm.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viral Infections in Solid Organ and Hematopoietic Stem Cell Transplantation

Abstract: Respiratory viruses are common in solid organ and hematopoietic stem cell transplant recipients and a recognized cause of significant morbidity and mortality. Epidemiology, risk factors, and attributable mortality in both populations are reviewed. In addition, virus-specific prevention and treatment options, including emerging investigational therapies, are discussed for respiratory syncytial virus, influenza, adenovirus, parainfluenza, and other respiratory viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 220 publications
(180 reference statements)
3
54
0
2
Order By: Relevance
“…23,27 In this study, a large proportion of CA-RVs except seasonal influenza resulted in symptomatic respiratory infection at a late posttransplant period, with median of 20 months in HSCT and 30 months in SOT recipients. Like as previous reports, 1,2,4,9,10,28 our data also showed that the posttransplant period in which CA-RVI occurred in SOT recipients was significantly longer than that in HSCT recipients. This finding suggests that physicians need to suspect and diagnosis CA-RVI in transplant recipients with respiratory symptoms regardless of posttransplant period.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…23,27 In this study, a large proportion of CA-RVs except seasonal influenza resulted in symptomatic respiratory infection at a late posttransplant period, with median of 20 months in HSCT and 30 months in SOT recipients. Like as previous reports, 1,2,4,9,10,28 our data also showed that the posttransplant period in which CA-RVI occurred in SOT recipients was significantly longer than that in HSCT recipients. This finding suggests that physicians need to suspect and diagnosis CA-RVI in transplant recipients with respiratory symptoms regardless of posttransplant period.…”
Section: Discussionsupporting
confidence: 90%
“…19 The epidemiology and clinical outcome of adenovirus (AdV), human metapneumovirus (hMPV), parainfluenza (PIV), and RSV in SOT and HSCT recipients have been reported during the past few decades. 4,19 However, there are few reports of unique features and impact on outcome or mortality of CA-RVI in non-transplant critically ill patients in ICU compared to transplant recipients, even though many reports have focused on the comparison of specific CA-RVI, particularly seasonal influenza virus, between SOT and HSCT recipients. 19 The clinical information of CA-RVI between these susceptible groups will be helpful to clinicians if they need to consider the different strategies or practices for treating CA-RV, especially in severe LRTI cases, among transplant recipients or non-transplant critically ill patients in ICU.…”
Section: Introductionmentioning
confidence: 99%
“…118,119 ALS-8176 (lumicitabine), an RNA polymerase inhibitor, was associated with a reduction in viral load and clinical severity compared with placebo in a phase II RSV challenge study in healthy adults, 120 although the role of this and other agents awaits clarification in target populations. There are a few investigational agents in phase II study in HCT recipients, namely ALX-0171, a nanobody fusion inhibitor (https://clinicaltrials.gov/ct2/show/NCT03418571 and https://clinicaltrials.gov/ct2/ show/NCT03468829) 1,16 and PC786, a non-nucleoside RSV L protein polymerase inhibitor (https://clinicaltrials.gov/ct2/show/study/NCT03715023). No RSV vaccine is currently available, although clinical trials are ongoing.…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…27 In contemporary studies that use molecular diagnostic techniques, rhinovirus is the most frequently detected RVI in HM patients and HCT recipients. 1,2,4,8,25,27 It is important to recognize the limitation of the current diagnostic platforms in the inability to differentiate between rhinovirus and enterovirus.…”
Section: Rhinovirusmentioning
confidence: 99%
“…Well‐documented sites of HAdV persistence include particularly tonsillar and adenoidal T‐lymphocytes, which appear to represent a sanctuary for adenoviruses, although other sites may also be involved . Hence, in contrast to many other community‐acquired respiratory viruses, adenoviral infections can occur both by exogenous acquisition and reappearance of persistent endogenous virus; however, the latter appears to be far more prevalent in immunocompromised individuals . Recipients of allogeneic haematopoietic stem cell transplantation (HSCT) represent one of the most vulnerable patient groups due to the severely impaired function of their immune system.…”
Section: Introductionmentioning
confidence: 99%